Rethinking police complaints - Smith, Graham (The British journal of criminology, 2004)
Procedures for dealing with complaints against the police have been at the centre of police reform for the last half-century. This paper departs from the traditional who investigates' approach and managerial orthodoxy to consider the primary functions of the complaints process. Four causes of complaint are identified - unprofessional behaviour, criminal conduct, tortious action and unacceptable policy - and four functions are considered - managerial, liability, restorative and accountability. It is concluded that in order to effectively and efficiently deal with the various causes of complaint, a two-tier system is required to deal with complaints that allege unprofessional behaviour and criminal conduct, and a third, separate tier, is necessary to consider complaints regarding unacceptable police policy